Chronic Pain after Open Appendectomy and Its Effects on Quality of Life in Children Aged 8–18 Years - Onur Palabiyik; Gurkan Demir (Pain Research and Management)
Background. Chronic postsurgical pain is an important problem for both children and adults. This study aims to investigate the prevalence of chronic postappendectomy pain (CPAP) in children and its social and physical effects. Methods. This prospective observational study was conducted on children aged 8–18 years who had undergone open appendectomies. In the sixth month after the surgical procedure, the presence of chronic pain was examined in the lower right abdominal area. CPAP and its effects on children’s daily life activities were assessed using the numeric rating scale (NRS) and the Pediatric Quality of Life Scale (PedsQL). Results. Analysis was performed on 158 children, 97 of whom were boys (61.4%) and 61 were girls (38.6%). The average age was 12.8 ± 3 years, the average NRS was 4.48 ± 1.1, and the average scar length was 6.09 ± 1.6 cm. Twenty-nine children described CPAP, and its prevalence at six months after the surgery was 18.4%. Of these, 16 (55.2%) complained of pain only during exercise and 13 (44.8%) experienced pain while resting. The rate of CPAP was significantly higher in girls. Female gender and longer scar length were associated with the development of chronic pain. The PedsQL scores from the children’s self-reports and their parents’ reports were significantly lower for children who described CPAP as compared to those without CPAP. Conclusion. CPAP occurs quite frequently in children, especially in girls, and negatively affects children’s quality of life.